The Relationship Between Birth Distance and Perineal Rupture Incident - Eka Marta Puspita Rini; Euvanggelia Dwilda Ferdinandus; Sofia Al Farizi; Andriyanti Andriyanti (Jurnal sosial dan sains, 2024)
Background: Perineal rupture was a quite serious problem. Factors that influence the incidence of perineal rupture were parity, birth spacing, fetal position, birth weight. Birth spacing of less than 2 years was considered high risk because it can cause complications during childbirth Purpose: The aim of this research was to know relationship between birth spacing and the incidence of perineal rupture Method: Design of this research was quantitative analytic retrospective. Population in this study was 268 medical records of mothers giving birth at Private Midwife Practice Place Sudjiati Frans Surabaya and the sample size was 160. Sampling technique used purposive sampling. Instrument used in this research was medical records at Midwife Practice Place Sudjiati Frans Surabaya for the period January – December 2022. Data were analyzed using pearson correlation test. Results: : Based on the results of pearson correlation with α = 0.05, the value of p = 0.001 (p < α) was obtained, which shows that there was a significant relationship between birth spacing and the incidence of perineal rupture in mothers giving birth. Conclusion: Birth interval had a significant relationship with the incidence of perineal rupture at Private Midwife Practice Place Sudjiati Frans Surabaya